2022
DOI: 10.1002/jhbp.1146
|View full text |Cite
|
Sign up to set email alerts
|

JPNclinical practice guidelines 2021 with easy‐to‐understand explanations for the management of acute pancreatitis

Abstract: Background In preparing the Japanese (JPN) guidelines for the management of acute pancreatitis 2021, the committee focused the issues raised by the results of nationwide epidemiological survey in 2016 in Japan. Method In addition to a systematic search using the previous JPN guidelines, papers published from January 2014 to September 2019 were searched for the contents to be covered by the guidelines based on the concept of GRADE system. Results Thirty‐six clinical questions (CQ) were prepared in 15 subject ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 166 publications
0
33
0
Order By: Relevance
“…Therefore, a minimally invasive procedure called video‐assisted retroperitoneal debridement (VARD) has been developed for WON, in which necrosectomy is performed via a retroperitoneal approach under laparoscopic assistance. A meta‐analysis of cohort studies reported that morbidity and mortality rates were significantly lower with VARD than with open necrosectomy 7 . However, although various minimally invasive approaches have been developed, there are limited data on the usefulness of these treatments for large WONs (i.e., more than 15 cm).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, a minimally invasive procedure called video‐assisted retroperitoneal debridement (VARD) has been developed for WON, in which necrosectomy is performed via a retroperitoneal approach under laparoscopic assistance. A meta‐analysis of cohort studies reported that morbidity and mortality rates were significantly lower with VARD than with open necrosectomy 7 . However, although various minimally invasive approaches have been developed, there are limited data on the usefulness of these treatments for large WONs (i.e., more than 15 cm).…”
mentioning
confidence: 99%
“…Moreover, if a large WON with an extensive amount of necrotic tissue is asymptomatic and sterile, spontaneous resolution without drainage can be expected in some cases. Therefore, prevention of infection starting in the early stages of pancreatitis is important, and the effectiveness of early enteral nutrition is recognized 7 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in several surveys ( 6 , 7 ), poor compliance was reported in terms of nutrition and prophylactic antibiotics. Further attempts are necessary to facilitate easy use of guidelines such as pancreatitis bundles provided in the Japanese clinical practice guidelines ( 8 ).…”
mentioning
confidence: 99%